(untitled) (Journal of Bangladesh Academy of Sciences, 2022)
An experiment was conducted with three levels of salinity (0, 60, and 120 mM NaCl) and four levels of silicon (0, 5, 10, and 20 mM) in petridish. All the growth parameters were decreased gradually with increasing salt concentration, whereas increasing silicon concentration progressively increased the parameters up to 10 mM Si across all the salt concentrations. The beneficial role of Si was noticed both in saline and non-saline conditions. Silicon application in the growth medium dramatically reduced shoot Na content, making plants tolerant to salt stress. J. Bangladesh Acad. Sci. 45(2); 251-253: December 2021